The effect of isokinetic exercises in developing the special strength for volleyball players - ALjaf, Dirya; Nooraldeen, Samah (Journal of Physical Education, 2023)
The research aimed to study the effect of isokinetic exercises in developing the special strength for volleyball players. The research sample included (15) volleyball players from the Muqdadiya Sports Club in Diyala Governorate for the youth category, and they were divided equally into two groups, control and experimental. the training program was applied to the experimental group for a period of two months, (3) training units per a week. the study concluded that exercises similar to the isokinetic method affected significantly in developing the special strength of volleyball players In an interesting way as well as to develop their skills better.